Comparison Of The Effectiveness Of High Intensity Laser Therapy (HILT) And Low-Level Laser Therapy (LLLT) On Improving Balance In Knee Osteoarthritis - Kukuh Wibisono; Rudy Handoyo; Erna Setiawati (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : Osteoarthritis (OA) of the knee is a joint disease with a high prevalence among the elderly. OA can cause balance disorders, which are one of the main causes of falls in the elderly. Balance can be measured using several scoring systems, one of which is the Berg Balance Scale (BBS). One of the treatment modalities for OA is laser therapy which is non-invasive and easy to apply. Low level laser therapy (LLLT) has been widely used in patients with knee OA, but recently high intensity laser therapy (HILT) has begun to be used in physical therapy with advantages over a wider range and depth. AIMS :  to compare the effect of LLLT and HILT therapy on improving functional balance in the elderly with knee OA. METHOD : This research is a randomized controlled trial pre-test and post-test-controlled group design. The sampling method used in this study is the simple random sampling method. The sample size was 27 subjects and divided into two groups, the LLLT group (n=14) and the HILT group (n=13). Each subject received laser therapy sessions 2 times a week for 4 weeks. Balance was assessed using the BBS before and after the intervention. RESULT :  There was an increase in BBS scores before and after treatment in the HILT group (p<0.001) and in the LLLT group (p<0.001), with the increase in the HILT group (7.79 ± 2.16) significantly greater than in the LLLT group (3 .08 ± 0.76) (p<0.001). CONCLUSION : HILT improves balance score better than LLLT.